Ionic liquid dispersed highly conducting polymer electrolyte for supercapacitor application: current scenario and prospects “ICSEM 2021” - Mathela, Shreya; Kumar, Sushant; K Singh, Pramod; Singh, Ram Chandra; Shukla, PK; Singh, Vijay; Mohd Noor, Ikhwan Syafiq (SAGE Publications, 2022)
Ionic liquid (IL) is now being considered as a novel contender in the development of highly conducting polymer electrolytes rather than a solvent. It has a significant impact on the electrochemical performance of polymer electrolytes. This study emphasizes the significance of low viscosity IL dispersion within a polymer (PVA) matrix. The electrical, structural and photoelectrochemical properties of the IL-doped polymer electrolyte are discussed in detail. These highly conducting IL doped solid polymer electrolytes show promise towards the development of highly efficient supercapacitors.